Генетические карты микроорганизмов: справочное пособие / И. А. Захаров, Б. П. Мацелюх - Захаров Илья Артемьевич (Наукова думка, 1986)
Экземпляры: КХ (20170503) / Инвентарный номер: 888522 / Сис.шифр: 576.8 / Авт.знак: З-38 / ГРНТИ: 34 / ББК: 28